91.0k views
0 votes
5. -6(7k + 11) =
What is the simplified expression?

User Debadatt
by
5.7k points

2 Answers

2 votes

Answer:

-6(7k + 11) = -49k - 66

Step-by-step explanation:

We need to distribute the -6 so that we can get rid of the parentheses.

To do that, we must multiply -6 by each term that is inside the parentheses

-6 * 7k = -49k

-6 * 11 = -66

Let's put that together.

-49k - 66

So, -6(7k + 11) = -49k - 66

User Chetan Kinger
by
5.8k points
0 votes

Answer:

=
{\boxed{\rm{ -42k - 66}}}

Step-by-step explanation:


\rm{= -6(7k + 11)}


\rm{= (-6) (7k + 11)}


\rm{= (-6) (7k) + (-6) (11)}

=
{\boxed{\rm{ -42k - 66}}}

Therefore, -42k - 66 is the required simplified form.

User Jesse Mcconnell
by
6.0k points